2012
DOI: 10.1053/j.tcam.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis in Cats

Abstract: Pancreatitis was considered a rare disease in the cat until a couple of decades ago when several retrospective studies of severe acute pancreatitis were published. It was apparent that few of the diagnostic tests of value in the dog were helpful in cats. With increasing clinical suspicion, availability of abdominal ultrasonography, and introduction of pancreas-specific blood tests of increasing utility, it is now accepted that acute pancreatitis is probably almost as common in cats as it is in dogs, although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 42 publications
1
72
2
5
Order By: Relevance
“…Similarly, traditional assays of lipase activity are widely described to be unreliable due to poor sensitivity and specificity. During the recent years, assays that specifically measure the pancreatic lipase activity (known as fPLI or Spec fPL) became available and are currently considered to be the most accurate blood tests for diagnosing pancreatitis in cats (Steiner et al, 2004;Forman et al, 2009;Armstrong and Williams, 2012). One study reported an overall sensitivity of fPLI for pancreatitis of 67% (100% for moderate to severe pancreatitis and 54% for mild pancreatitis).…”
Section: Pancreatic Enzymesmentioning
confidence: 96%
See 3 more Smart Citations
“…Similarly, traditional assays of lipase activity are widely described to be unreliable due to poor sensitivity and specificity. During the recent years, assays that specifically measure the pancreatic lipase activity (known as fPLI or Spec fPL) became available and are currently considered to be the most accurate blood tests for diagnosing pancreatitis in cats (Steiner et al, 2004;Forman et al, 2009;Armstrong and Williams, 2012). One study reported an overall sensitivity of fPLI for pancreatitis of 67% (100% for moderate to severe pancreatitis and 54% for mild pancreatitis).…”
Section: Pancreatic Enzymesmentioning
confidence: 96%
“…Palpation may or may not elicit a response of pain. Severe acute or acute on chronic pancreatitis may be associated with dehydration, tachycardia, tachypnea, and icterus; cats may be hypothermic; fever is also possible but less common (Armstrong and Williams, 2012;Caney, 2013). For more details on pancreatitis, see Types of Diabetes in Cats and the discussion on pancreatic enzymes in Clinical Pathology.…”
Section: Physical Examinationmentioning
confidence: 97%
See 2 more Smart Citations
“…Steroids are no longer included in the list of drugs suspected of being associated with pancreatitis (Armstrong and Williams, 2012;Mansfield, 2012). Steroids are no longer included in the list of drugs suspected of being associated with pancreatitis (Armstrong and Williams, 2012;Mansfield, 2012).…”
Section: Pancreatitismentioning
confidence: 99%